Economic crises, health and education in Jamaica - Kim, Namsuk; Serra García, Marta (Estudios Económicos de El Colegio de México, 2010)
We study the impact of growth fluctuation education and health indicators in Jamaica. Using household surveys between 1989 and 2007, we study the impact by using pseudo-panel regressions at the parish level, instrumenting growth fluctuations with variations in major Jamaican export commodities, to account for the endogeneity of growth in its relationship with education and health indicators. The main finding of the instrumental variable regression is that GDP fluctuation has mixed impacts on education and health.